The Regulation Mechanism of MUC5AC Secretion in Airway of Obese Asthma: MUC5AC in Airway of Obese Asthma - Li, Tingtian; Wang, Yafei; Huang, Shujuan; Tang, Huaping (Cellular and Molecular Biology, 2022)
The purpose of this study was to establish a rat asthma model and extract MUC5AC to explore the mechanism of mucin 5AC (MUC5AC) signaling pathway regulating the function of asthmatic airway smooth muscle cells (ASMC) and participating in asthmatic airway remodeling. Western blot was used to detect β-catenin (β-catenin), glycogen synthase kinase-3β (GSK-3β), proto-oncogene MUC5AC and cyclin D1 (cyclin D1) in MUC5AC of asthmatic and normal groups. After inhibiting the interaction between β-catenin and transcription cofactor p300 / CBP in ASMC of the asthma group and control group, the cell viability and cycle changes of ASMC were detected by the CCK-8 method and flow cytometry. After inhibiting the activity of P38 mitogen-activated protein kinase (MAPK), the protein expression changes of c-Myc and cyclin D1 were detected by Western blot. Results showed that comprehensive HE staining results of lung tissue sections indicate that the experimental rat model of asthma airway remodeling was successfully established. Compared with the control group, 100 fxmol and L1 Efaroxan promoted insulin secretion (P <0.01), and administration of the MUC5AC antagonist KU14R significantly inhibited the effect of MUC5AC.Western blot showed that the protein expression levels of β-catenin, c-Myc and cyclin D1 in ASMC of the obese asthma group were significantly higher than those of the control group (P <0.05), while the protein expression level of GSK-3β was lower than Control group (P <0.05). After inhibiting the interaction between β-catenin and p300 / CBP, the decrease in cell viability and the degree of cell cycle change of ASMC in the asthma group were more obvious than those in the control group (P <0.05). After inhibiting the activity of P38 MAPK, the expressions of the target proteins c-Myc and cyclin D1 in the MUC5AC signaling pathway in ASMC model rats and control rats were down-regulated, and the difference was statistically significant (P <0.05). The conclusion was that the Wnt/β-catenin signaling pathway can regulate the proliferation and differentiation of ASMC by up-regulating the expression level of cMyc. Cyclin D1 interacts with the MAPK signaling pathway, thereby affecting the function of ASMC and participating in asthma airway remodeling.